2013
DOI: 10.3174/ajnr.a3427
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Posterior Periventricular Nodular Heterotopia: A Recognizable Cortical Malformation with a Spectrum of Associated Brain Abnormalities

Abstract: BACKGROUND AND PURPOSE:Bilateral posterior PNH is a distinctive complex malformation with imaging features distinguishing it from classic bilateral PNH associated with FLNA mutations. The purpose of this study was to define the imaging features of posterior bilateral periventricular nodular heterotopia and to determine whether associated brain malformations suggest specific subcategories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
(39 reference statements)
2
39
0
Order By: Relevance
“…Bilateral PVNH is often due to mutations in FLNA (3-6); however, in many cases and phenotypic subgroups of PVNH (38), the genetic aetiology is not known. Gross anatomical consequences on brain development that are a result of genetic mutations, are often readily visible on structural MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral PVNH is often due to mutations in FLNA (3-6); however, in many cases and phenotypic subgroups of PVNH (38), the genetic aetiology is not known. Gross anatomical consequences on brain development that are a result of genetic mutations, are often readily visible on structural MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a few nodules lie immediately adjacent to the ventricular wall or a few millimeters away from it; the neurons may be arranged in a pattern suggestive of laminar organization (Garbelli et al 2009), and they contain primarily later-born neurons (Ferland and Guerrini 2009). PNH is often associated with other malformations, which vary with the location of the heterotopia; patients with posterior (trigonal, occipital, and temporal horns) PNH have a high incidence of cerebellar dysgenesis, corpus callosum anomalies, under-rotated hippocampi, and temporal lobe cortical dysgenesis of various types (Pisano et al 2012;Gonz谩lez et al 2013;Mandelstam et al 2013). More complex forms include subcortical heterotopia, which are a continuous, often swirling conglomeration of neurons that extend from the ependyma to the cortex; a subset of these contain colony-stimulating factor (CSF) and blood vessels and are continuous with the subarachnoid space (Barkovich 2000).…”
Section: Gray Matter Heterotopiamentioning
confidence: 99%
“…9 The presence of SEH also demonstrates a strong association with other structural anomalies in the brain in addition to Chiari malformation, including cerebral cortical malformations, callosal anomalies, and decreased white matter volume. [10][11][12] However, very little radiology literature has reported on the detection of SEH on fetal MR imaging, with only case reports and a few small case series described. [13][14][15] Many authors believe that SEH can be identified on fetal MR imaging.…”
mentioning
confidence: 99%
“…7 Although the exact implications in this subset of patients are still under investigation, ample reports in the literature describe the clinical relevance of SEH. [8][9][10][11][12] Up to 80% of patients with SEH have been reported to develop epilepsy during their lifetimes, and disorders of cognition are seen in anywhere from 20% to 60%. 9 The presence of SEH also demonstrates a strong association with other structural anomalies in the brain in addition to Chiari malformation, including cerebral cortical malformations, callosal anomalies, and decreased white matter volume.…”
mentioning
confidence: 99%